PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN MAMUJU UTARA - Isnada, Indah (Katalogis, 2016)
The aim of this study; (1) to determine the effect of organizational culture simultaneously the performance of employees in the Secretariat of North Mamuju regency; (2) to determine the effect of organizational culture partially on the performance of employees in the Secretariat of the Regional District of North Mamuju. Organizational culture theory used from Denison, while the theoretical performance of Robbins. This type of research with a quantitative survey approach. The study population is employees of the Secretariat of the Regional District of North Mamuju totaling 148 people were drawn using the formula to 60 respondents. Data collection techniques include observation, questionnaires, and documentation, while the technique of data analysis using multiple linear regression. The results showed; (1) the influence of organizational culture simultaneously the performance of employees in the Secretariat of the Regional District of North Mamuju determined by adaptability (adaptability), consistency (consistency), involvement (engagement), danmission (mission) .Besar effect obtained with 62.2% the level of the strong relationship between the variables. While the descriptive results indicate that the dimension that has the highest percentage value is the mission (mission) with a percentage of 82.22% which means all members of the organization have the same objectives in terms of vision and mission, while the lower dimension is adaptability (adaptability) with a percentage of 67, 33%, which means that the employee has not been able to learn from mistakes that it faces in its work; (2) the influence of organizational culture partially on the performance of employees in the Secretariat of the Regional District of North Mamuju determined by the influence of adaptability (adaptability) to employee performance, the effect of consistency (consistency) to employee performance, the effect of involvement (engagement) to employee performance, and influence mission (mission) to employee performance.